1993
DOI: 10.1073/pnas.90.14.6844
|View full text |Cite
|
Sign up to set email alerts
|

cdc2-like kinase from rat spinal cord specifically phosphorylates KSPXK motifs in neurofilament proteins: isolation and characterization.

Abstract: p34cdc2 kinase mRNA levels during the terminal differentiation of neurons (13), demonstration ofNF-H phosphorylation by p34Cdc2 kinase from nonneuronal sources, while intriguing, has uncertain physiologic relevance. The presence of consensus sequences of substrate for p34cdc2 kinase on vertebrate NF-H suggests the possibility that there may be cdc2-related kinases in the nervous system that phosphorylate these motifs.In this report, we present the purification, biochemical, and immunologic characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
180
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(187 citation statements)
references
References 22 publications
7
180
0
Order By: Relevance
“…However, transfection experiments failed to demonstrate phosphorylation of NF-H by GSK3 (Sun et al, 1996), suggesting the existence of additional requirements for in vivo phosphorylation by this kinase. In contrast, evidence based on synthetic peptides and recombinant, truncated NP-H constructs suggests that cdk5 is more selective, phosphorylating only sites of the consensus S/TPX 1KX2, especially where X, is not acidic (Hisanaga et a!., 1991; Beaudette et a!., 1993;Shetty et a!., 1993;Sun et a!., 1996). Three of the S/TP sites in chicken NF-M conform to this motif (Ser 575, Ser552, and Ser715).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, transfection experiments failed to demonstrate phosphorylation of NF-H by GSK3 (Sun et al, 1996), suggesting the existence of additional requirements for in vivo phosphorylation by this kinase. In contrast, evidence based on synthetic peptides and recombinant, truncated NP-H constructs suggests that cdk5 is more selective, phosphorylating only sites of the consensus S/TPX 1KX2, especially where X, is not acidic (Hisanaga et a!., 1991; Beaudette et a!., 1993;Shetty et a!., 1993;Sun et a!., 1996). Three of the S/TP sites in chicken NF-M conform to this motif (Ser 575, Ser552, and Ser715).…”
Section: Discussionmentioning
confidence: 99%
“…These include casein kinase I Hollander et al, 1996) and at least three different Pro-dependent kinases: protein kinase FA/glycogen synthase kinase-3 (GSK3; Guan et al, 1991), cyclin-dependent kinases (Hisanaga et al, 1991;Guan et al, 1992;Lew et a!., 1992;Shetty et al, 1993;Sun et a!., 1996), and mitogenactivated protein kinase (ERK kinase; Roder and Ingram, 1991;Chertoff et al, 1995). The phosphorylation sites are mostly in Ser residues in Lys-Ser-Pro (KSP) sequences (Geisler et a!., 1987;Lee et a!., 1988), which are repeated as many as 60 times in mammalian NF-H. Other, less frequently repeated, potential phosphorylation motifs have also been recognized, especially in NF-M, including KXSP and KXXSP (Shaw, 1991).…”
mentioning
confidence: 99%
“…Transfection studies using COS-7 cells show that these residues are also phosphorylated in vivo. Although it has been shown that Cdk5 specifically phosphorylates peptides containing X(S/T)PXK motifs (where X represents a neutral/basic residue) (55,56), the ability of Cdk5 to phosphorylate this novel (SPRXR) consensus sequence motif in ErbB3 raises the possibility that Cdk5 targets other proteins in the nervous system than X(S/T)PX(K/R). In addition, this study suggests that Cdk5 is involved in the regulation of receptor protein-tyrosine kinases affecting downstream signaling transduction pathways in neuronal development and survival (Fig.…”
Section: Fig 6 Cdk5 Involved In Neuregulin-induced Phosphorylation mentioning
confidence: 99%
“…The purified protein kinase contains 33-and 25-kDa subunits; the 33-kDa subunit was later identified as the Cdc2-related kinase Cdk5 (16). Cdk5 was similarly identified as a neuronal protein kinase capable of phosphorylating the KSPXK sequence motif in neurofilament proteins NF-H, NF-M (17)(18)(19), and the tau protein (20). Phosphorylation of tau by Cdk5 is particularly interesting because abnormally phosphorylated tau is the major component of the paired helical filaments, which accumulate in the brains of Alzheimer patients (21).…”
mentioning
confidence: 99%